Marine Threats Overlap Key Foraging Habitat for Two Imperiled Sea Turtle Species in the Gulf of Mexico - Hart, Kristen M.; Iverson, Autumn R.; Fujisaki, Ikuko; Lamont, Margaret M.; Bucklin, David; Shaver, Donna J. (Frontiers in Marine Science, 2018)
Effective management of human activities affecting listed species requires understanding both threats and animal habitat-use patterns. However, the extent of spatial overlap between high-use foraging areas (where multiple marine species congregate) and anthropogenic threats is not well known. Our modeling approach incorporates data on sea turtle spatial ecology and a suite of threats in the Gulf of Mexico to identify and map “hot spots” of threats to two imperiled turtle species. Of all 820 “high” threats grid cells, our tracked turtles foraged at least one day in 77% of them. Although threat data were not available outside the U.S. Exclusive Economic Zone, our map of turtle and threat “hotspots” can be incorporated in future more comprehensive threat analyses for the region. Knowledge of these shared foraging- and threat-areas can assist managers charged with designing effective conservation and population recovery strategies, in future habitat modeling efforts, and in designations of Gulf of Mexico habitat with high conservation value.